Results of Adrenalectomy for Isolated, Metachronous Metastasis of Breast Cancer: A Retrospective Cohort Study - Illuminati, Giulio; Pasqua, Rocco; D'Ermo, Giuseppe; Girolami, Marco; Cerbelli, Bruna; D'Amati, Giulia; Carboni, Fabio; Fiori, Enrico (Frontiers in Surgery, 2021)
Background and aim. Metachronous, isolated adrenal metastases from breast cancer are extremely rare. The aim of this study was to evaluate the results of adrenalectomy as a treatment of this uncommon condition. Methods. Twelve female patients (median age: 68 years) underwent 13 adrenalectomies for isolated, metachronous metastases of breast cancer. Ten resections were performed thorugh open surgery and two were preformed through a laparoscopic approach. As main study endpoints, postoperative mortality, postoperative morbidity and disease-free survival were considered. Median length of follow-up was 40 months. Results. Postoperative mortality was absent. Postoperative morbidity was 17%: one patient presented a postoperative pneumothorax requiring drainage and one patient required re-hospitalization 8 days after contralateral adrenalectomy for electrolyte imbalance. Two patients died of recurrent metastatic disease, 28 and 33 months respectively after adrenalectomy. One patient remained alive with hepatic metastases at 32 months from resection of adrenal recurrence. All in all, disease-free survival at 48 months was 75%. Conclusions. Adrenalectomy for metachronous, isolated metastases of breast cancer can be performed with no postoperative mortality and minimal postoperative morbidity, enabling good long-term disease-free survival.